Addressing challenges of quantitative methodologies and event interpretation in the study of atrial fibrillation. (September 2019) - Ciaccio, Edward J.; Wan, Elaine Y.; Saluja, Deepak S.; Acharya, U. Rajendra; Peters, Nicholas S.; Garan, Hasan
Highlights: The mechanisms of Atrial Fibrillation (AF) are imprecisely known. AF drivers likely consist of premature stimuli and rotational features. These drivers are not well localized and ablated to stop AF. Quantitative models can be implemented to estimate driver properties. Driver properties may be useful to direct catheter ablation. Abstract: Atrial fibrillation (AF) is the commonest arrhythmia, yet the mechanisms of its onset and persistence are incompletely known. Although techniques for quantitative assessment have been investigated, there have been few attempts to integrate this information to advance disease treatment protocols. In this review, key quantitative methods for AF analysis are described, and suggestions are provided for the coordination of the available information, and to develop foci and directions for future research efforts. Quantitative biologists may have an interest in this topic in order to develop machine learning and tools for arrhythmia characterization, but they may perhaps have a minimal background in the clinical methodology and in the types of observed events and mechanistic hypotheses that have thus far been developed. We attempt to address these issues via exploration of the published literature. Although no new data is presented in this review, examples are shown of current lines of investigation, and in particular, how electrogram analysis and whole-chamber quantitative modeling of the left atrium may be useful to characterize fibrillatory patterns of activity, so as to propose avenues for more efficacious acquisition and interpretation of AF data.